2015
DOI: 10.1111/jan.12832
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between breastfeeding and postnatal depression: the role of pain and physical difficulties

Abstract: AimsTo examine the relationship between specific reasons for stopping breastfeeding and depressive symptoms in the postnatal period.BackgroundDifficulty breastfeeding has been connected to postnatal depression although it is unclear whether difficulty breastfeeding precedes or succeeds a diagnosis. However, the concept of ‘breastfeeding difficulty’ is wide and includes biological, psychological and social factors.DesignA cross‐sectional self‐report survey.MethodsData were collected between December 2012 and Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
128
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(163 citation statements)
references
References 64 publications
10
128
1
14
Order By: Relevance
“…Nipple pain, perceived low supply, and expressing (pumping) of breastmilk are known to negatively affect breastfeeding duration 32, 33, 34. Pain and low supply have also been linked with an increased likelihood of women experiencing symptoms of anxiety and depression 8. This study reinforced that these were important issues experienced by a significant number of women in the community, not only those seeking breastfeeding support.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Nipple pain, perceived low supply, and expressing (pumping) of breastmilk are known to negatively affect breastfeeding duration 32, 33, 34. Pain and low supply have also been linked with an increased likelihood of women experiencing symptoms of anxiety and depression 8. This study reinforced that these were important issues experienced by a significant number of women in the community, not only those seeking breastfeeding support.…”
Section: Discussionmentioning
confidence: 52%
“…A number of other researchers have also found that perceived low supply is the main reason for women reducing or ceasing breastfeeds 33, 36, as well as for expressing (pumping) breastmilk 18, 33, 36 and bottle feeding 37. Clinicians should be aware of the common misconceptions about adequacy of milk supply and actively dispel these when appropriate because breastfeeding problems have been linked to an increased risk of postnatal depression 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Brown et al [79] found that breastfeeding cessation is correlated with high depression scores in mothers, but when examining this correlation more closely found that it was only present in mothers who stopped breastfeeding due to physical difficulty and pain when breastfeeding. Another study assessed breastfeeding complications and maternal mood at 8 weeks postpartum and found that breastfeeding problems alone, or co-morbid with physical problems, were associated with poorer maternal mood [80].…”
Section: Psychological Effects Of Breastfeeding In Mothersmentioning
confidence: 99%
“…Doctors have great potential to influence behaviour, and yet training in lactation support is almost entirely absent from undergraduate or postgraduate paediatric training programmes, and attitudes can be influenced by difficult personal experiences 14. Normal neonatal behaviour (cluster feeding, frequent waking to feed) may not be understood, and breastfeeding can be hard to establish; in specific circumstances, breastfeeding is impossible.…”
mentioning
confidence: 99%